Investigation on alkalinity reduction methods of eco‐porous concrete. Issue 9 (3rd September 2018) - Yang, J.W.; Gao, T.; Yin, J.; Wu, S.Y.; Liang, Q.
Abstract: Laboratory tests were conducted to investigate the different alkalinity reduction methods. Single alkalinity‐reduced treatment and hybrid alkalinity‐reduced method were employed respectively. Single alkalinity‐reduced treatment methods include oxalic acid soaking, oxalic acid spraying and deep penetrating sealer (DPS) spraying. The hybrid alkalinity‐reduced method used silica fume (SF) and ferrous sulfate. Deep penetrating sealer spraying and rapid carbonization were performed in the hybrid alkalinity‐reduced treatment. The compressive strength and alkalinity of eco‐porous concrete were evaluated by employing different alkalinity‐reduced methods. The results showed that effect of single alkalinity‐reduced treatment on the strength of eco‐porous concrete is not obvious. The 28‐day compressive strength of the specimens was 7.8 MPa ‐ 10.3 MPa and the pH value was about 10.4. By using hybrid alkalinity‐reduced method, the rapid carbonization and alkali solidification gave the best performance in strength and alkalinity reduction. The 28‐day compressive strength was 8.1 MPa and pH value was reduced to 10.0.